Management of odontogenic cervicofacial infections presenting to oral and maxillofacial units during the first wave of the COVID-19 pandemic in the United Kingdom. Issue 8 (October 2021) - Puglia, F.A.; Ubhi, H.; Dawoud, B.; Magennis, P.; Chiu, G.A.
Abstract: On 25 March 2020, the Chief Dental Officer issued national guidance restricting the provision of all routine, non-urgent dental services in response to the spread of COVID-19. We analysed odontogenic cervicofacial infections (CFI) presenting to oral and maxillofacial surgery (OMFS) departments during the first wave of COVID-19 in the United Kingdom. From 1 April 2020 until 31 July 2020 a database was used to prospectively collect records for all patients with CFI who presented to oral and maxillofacial teams. Information gathered included clinical presentation, location/origin of infection, and how this was managed. The OMFS units were asked to compare the patient's care with the treatment that would usually have been given prior to the crisis. A total of 32 OMFS units recorded 1381 cases of CFI in the UK. Most of the infections were referred via the emergency department (74%). Lower first or second molars were the most common origin, contributing 40% of CFI. Collaborators reported that patients' treatments were modified as a response to COVID in 20% of cases, the most frequently cited reason being the application of COVID-19 hospital policy (85%). The impact of the first wave of COVID modified the management of a significant number of patients presenting with CFI, and there was a proactive move to avoid general anaesthetics where possible. Some patients who presented to secondary care were given no treatment, suggesting they could have been managed in primary dental care if this had been available. We recommend that OMFS units and urgent dental care centres (UDCCs) build strong communication links not only to provide the best possible patient care, but to minimise COVID exposure and the strain on emergency departments during the pandemic.